PENGARUH FASHION INVOLVEMENT, ATMOSFER TOKO DAN PROMOSI PENJUALAN TERHADAP IMPULSE BUYING PADA MATAHARI DEPARTMENT STORE DI KOTA DENPASAR - Temaja, I Komang Wisnu Bayu; Rahanatha, Gede Bayu; Yasa, Ni Nyoman Kerti (E-Jurnal Manajemen, 2015)
This study aims to find out the effect of fashion involvement, store atmosphere and sales promotion toward impulse buying in the Matahari Department Store, Denpasar city. Data was gained by spreading questioner with Likert scale to 119 respondents. This study used purposive sampling and multiple linear regression analysis. The result showed that fashion involvement have positive and significant effect toward impulse buying of fashion product in the Matahari Department Store, store atmosphere have positive and significant effect toward impulse buying of fashion product in the Matahari Department Store, and sales promotion have positive and significant effect toward impulse buying of fashion product in the Matahari Department Store.
Keywords: fashion involvement; store atmosphere; sales promotion; impulse buying